2018–2019 Florida Citrus Production Guide: Pesticides Registered for Use on Florida Citrus - Lauren M. Diepenbrock; Megan M. Dewdney; Tripti Vashisth; Stephen H. Futch (EDIS)
This 21-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. This document lists of products which are registered for use on citrus regardless of whether or not they are recommended for use. Written by L. M. Diepenbrock, M. M. Dewdney, T. Vashisth and S. H. Futch, and published by the Entomology and Nematology Department, May 2018.